A Preliminary Discussion on the Christianization of Fujian Union University, a Church-Affiliated Institution - CHEN Lingfei, (Journal of Research for Christianity in China (JRCC), 2025)
In the 19th century, Western missionaries began establishing schools in China to expand and develop Christian influence. Twenty-three church-affiliated universities emerged, with Fuzhou Union University in Fujian—located in the crucial missionary hub of Fuzhou—standing as a direct product of Christian missionary endeavors in China. Founded through the collaboration of four major Western missionary societies, the university initially drew heavily upon, and even replicated, the educational models and management philosophies of Western church-affiliated institutions. Throughout its academic pursuits, the university consistently prioritized Christian theological education and the promotion of Christian religious activities, thereby exhibiting distinct Christian characteristics. This paper conducts a case study of Fujian Union University, focusing on its preparatory process, educational mission, theological education, on-campus religious organizations, and religious activities. Centered on examining its “Christianization” features, it explores the profound influence of Christian culture on church-affiliated universities in China.